(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indiaissufferingfromgravescarcityofwaterduetoanincreaseindemandofwater.Whilethegovernmenthasproposedseveralgroundwaterrechargeschemes,itismoreimportanttofixtheproblemofover-exploitation.InIndia60%ofthewaterneedsismetbyusinggroundwater,thislevelchangesto90%inruralareaswherepeoplehighlyrelyonwellsandnaturallakes,rivers.Withincreaseinurbanization,commercializationanddevelopment,theuseofgroundwaterhasincreasedexplicitly.Studiesandreportsshowthatregionsarebecomingmorewaterstressedasscarcityanddepletionofwaterisontherise.Privatecompanieshavealsobeenoneofthemajorexploitersofwaterresources.peopleover-exploitwaterresourcesforpersonalgains.Inthispaper,theauthorshavediscussedtheapplicationofpublictrustdoctrineinprotectionofwaterresourcesinIndia.WeseektoanalysehowthedoctrineisappliedandwhetherthedoctrineisasolutiontotheproblemofwaterdepletioninIndia.